1999
DOI: 10.1089/ten.1999.5.317
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Analysis of a Chondrocyte-Based Repair Model of Articular Cartilage

Abstract: The objective of this study was to evaluate the biomechanical properties of newly formed cartilaginous tissue synthesized from isolated chondrocytes. Cartilage from articular joints of lambs was either digested in collagenase to isolated chondrocytes or cut into discs that were devitalized by multiple freeze-thaw cycles. Isolated cells were incubated in suspension culture in the presence of devitalized cartilage matrix for 3 weeks. Multiple chondrocyte/matrix constructs were assembled with fibrin glue and impl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
51
0
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 64 publications
(62 citation statements)
references
References 29 publications
9
51
0
2
Order By: Relevance
“…Previous studies of our group demonstrated the feasibility and the efficiency of bonding cartilaginous [25,26,28,32] and meniscal [27,29] tissue with cellular fibrin glue. According to this experience, we have designed the present study in order to evaluate the potential of chondrocytes-embedded fibrin glue for bonding meniscal slices in a nude mouse model.…”
Section: Discussionmentioning
confidence: 88%
“…Previous studies of our group demonstrated the feasibility and the efficiency of bonding cartilaginous [25,26,28,32] and meniscal [27,29] tissue with cellular fibrin glue. According to this experience, we have designed the present study in order to evaluate the potential of chondrocytes-embedded fibrin glue for bonding meniscal slices in a nude mouse model.…”
Section: Discussionmentioning
confidence: 88%
“…According to our previous experience with chondrocytes and fibrin glue [26][27][28][29][30], we have designed the present study in order to investigate the potential of a tissue engineered implant, made of chondrocytes expanded in vitro, fibrin glue, and a calcium-phosphate scaffold, for osteochondral repair. We have analyzed the macroscopic appearance of this composite and the resulting stiffness of the constructs after in vitro culture.…”
Section: Discussionmentioning
confidence: 99%
“…This study evaluated the morphologic characteristics of an in vitro tissue-engineered osteochondral composite designed to treat osteochondral lesions. Following our previous experience with chondrocyte-fibrin glue composites [17][18][19][20], we designed the present study to investigate the potential of a tissue-engineered implant, made of cultured chondrocytes, fibrin glue, and a calciumphosphate scaffold. The gross mechanical integrity of the fresh specimens, evaluated by probing with forceps, was consistent with cartilage formation.…”
Section: Discussionmentioning
confidence: 99%